Technostress Antar Pekerja Selama Pandemi Covid-19: Level Manajerial Versus Professional - ; Dina Mellita (Fakultas Seni Rupa dan Desain ITB, 2022)
This study aims to assess the differences in technostress received by workers at themanagerial level and professional workers during the COVID-19 pandemic. This studyuses a comparative research design concerning Techo-Overload, Techno-Invasion,Techno-Complexity, Techno-Insecurity, and Techno-Uncertainty between the twogroups of workers were studied. Questionnaires were distributed to 119 of workers.The results of the independent sample t-test showed that all the null hypotheses for the variables Techno-Overload, Techno-Invasion, Techno-Complexity, Techno- Insecurity, and Techno-Uncertainty were rejected, which means that there is no difference in technostress between workers at the managerial level and professional workers. Meanwhile, based on the Mann-Whitney U Test, it is known that the level of technostress measured only by Techo-Invasion has differences between the two groups of workers. The result indicates that the massive use of technology amid COVID-19 is disturbing the personal lives of workers at the managerial level.